Knockdown of Antisense Noncoding Mitochondrial Rna Reduces Tumorigenicity of Patient-Derived Clear Cell Renal Carcinoma Cells in an Orthotopic Xenograft Mouse Model - Borgna-Christie, V (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Clear cell renal cell carcinoma (ccRCC) is the most prevalent form of renal cancer and its treatment is hindered by a resistance to targeted therapies, immunotherapies and combinations of both. We have reported that the knockdown of the antisense noncoding mitochondrial RNAs (ASncmtRNAs) with chemically modified antisense oligonucleotides induces proliferative arrest and apoptotic death in tumor cells from many human and mouse cancer types. These studies have been mostly performed in vitro and in vivo on commercially available cancer cell lines and have shown that in mouse models tumor growth is stunted by the treatment. The present work was performed on cells derived from primary and metastatic ccRCC tumors. We established primary cultures from primary and metastatic ccRCC tumors, which were subjected to knockdown of ASncmtRNAs in vitro and in vivo in an orthotopic xenograft model in NOD/SCID mice. We found that these primary ccRCC cells are affected in the same way as tumor cell lines and in the orthotopic model tumor growth was significantly reduced by the treatment. This study on patient-derived ccRCC tumor cells represents a model closer to actual patient ccRCC tumors and shows that knockdown of ASncmtRNAs poses a potential treatment option for these patients. © 2024 by the authors.